Healthy Eating and Mental Resilience: A Study on Amateur Football Players - Aydemir, Isa; Erip, Necdet; Onat, Tugba; Aydin, Savas; Cali, Oguzhan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
This study aims to examine the relationship between amateur football players’ attitudes toward healthy eating and their mental toughness levels. A total of 157 amateur football players from Hakkâri participated in the study. Data on participants’ demographic information, sports history, and lifestyle were collected using the Personal Information Form. The Attitudes Toward Healthy Eating Scale was used to assess healthy eating habits, while the Mental Toughness Scale was used to measure mental toughness levels. The normality distribution of the data was evaluated using the Kolmogorov-Smirnov and Shapiro-Wilk tests. For normally distributed variables, an independent samples t-test and one-way analysis of variance (ANOVA) were applied. The Tukey HSD post-hoc test was used for variables with significant differences in ANOVA results. Pearson correlation analysis was conducted to determine the relationship between variables. The analyses showed a positive relationship between healthy eating and mental toughness. Age-based analyses revealed that football players aged 22 and above had higher mental toughness levels than those aged 21 and below. It was found that sleep patterns had a significant impact on mental toughness, with regularly sleeping players exhibiting higher mental toughness levels. The father’s education level was significantly related to the players’ nutritional knowledge and mental toughness levels. However, variables such as BMI, alcohol and tobacco use, years of licensing, and the mother’s education level were not significantly associated with attitudes toward healthy eating and mental toughness. In conclusion, developing healthy eating habits and maintaining a regular sleep schedule are crucial factors in enhancing athletes’ mental toughness. In this regard, it is recommended to implement healthy eating education and psychological programs that support mental toughness for athletes.